Penerapan Metode Simple Additive Weighting (SAW) dan Technique for Order Preference by Similarity to Ideal Solution (TOPSIS) dalam Pemilihan Perangkat Pribadi - Amalia Khansa; Fauziah Fauziah; Aris Gunaryati (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2021)
Along with the rapid development of technology, many types of laptops and smartphones have sprung up. The many types on the market can make consumers confused in choosing products. The decision support system for choosing this personal device uses the Simple Additive Weighting (SAW) method and the Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). The basic concept of this method is to find the weighted sum of the performance ratings for each alternative for all attributes. In the results of manual and system calculations, the SAW and TOPSIS methods produce the same ranking. In the SAW method, the highest-ranking of laptops is obtained by Acer Swift 3 (SF314-56G) with a value of 0.977 and on smartphones, the highest score is obtained by the Samsung Galaxy M51 with a value of 1. In the TOPSIS method, the highest-ranking is obtained by a laptop with a value of 0.9507 and a smartphone with a value of 1.